Xu Fuguan’s Concept of Anxiety and Its Connection to Religious Studies - Tea SERNELJ (Asian Studies, 2013)
Although Xu Fuguan (1903–1982) belongs to the most important representatives of the Modern Confucian intellectual movement, he is rather unknown outside China. However, his concept of “anxiety” (youhuan yishi 憂患意識) is not only relevant for the recognition of the special characteristics, which determines the ideological and political structure of ancient Chinese society, but also for the intercultural elaboration of Jaspers’s “axial age” theory. This article introduces this concept to the European academic readership, and provides an analysis of its connection to the Modern Confucian hypothesis regarding the absence of an external God (or Deities) in classical Chinese culture.